BIOMECHANICS IN SPORTS: PERFORMANCE ENHANCEMENT AND INJURY PREVENTION - Kumbhar, Rushikesh Chandrakant; Wangujare, Santosh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sports biomechanics, a significant element in sports, influences a player's performance and injury rate. Enhancing the performance of players without injuries is the primary goal of sports biomechanics. Sport biomechanics covers physiology, kinesiology, and physics in order to prevent injuries.